2003
DOI: 10.1086/374001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Protection of Mice against LethalStaphylococcus aureusInfection by Novel Bacteriophage φMR11

Abstract: The protective effects of bacteriophages were assessed against experimental Staphylococcus aureus infection in mice. Of the S. aureus phages isolated in the study, phi MR11 was representatively used for all testing, because its host range was the most broad and it carries no genes for known toxins or antibiotic resistance. Intraperitoneal injections (8 x 10(8) cells) of S. aureus, including methicillin-resistant bacteria, caused bacteremia and eventual death in mice. In contrast, subsequent intraperitoneal adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
169
3
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(184 citation statements)
references
References 43 publications
8
169
3
2
Order By: Relevance
“…Reports have revealed that a single treatment with phage leads to recovery in mice with infections caused by E. coli (34), P. aeruginosa (12), methicillin-resistant Staphylococcus aureus (24), and vancomycin-resistant Enterococcus faecium (6). In the present study, we also found that a single treatment with phage strain KPP10 prevented the death of mice after gutderived sepsis and intraperitoneal infection with P. aeruginosa.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Reports have revealed that a single treatment with phage leads to recovery in mice with infections caused by E. coli (34), P. aeruginosa (12), methicillin-resistant Staphylococcus aureus (24), and vancomycin-resistant Enterococcus faecium (6). In the present study, we also found that a single treatment with phage strain KPP10 prevented the death of mice after gutderived sepsis and intraperitoneal infection with P. aeruginosa.…”
supporting
confidence: 78%
“…Phage strain KPP10 was purified essentially by the procedure used for T4-type phages (24). P. aeruginosa strain D4 was used as the host, and the bacterial strain was suspended at 1 ϫ 10 8 cells/ml in 50 ml LB broth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings shows that appropriate administration can be used to treat lethal infectious diseases caused by Escherichia coli, Vibro cholerae, Staphylococcus aureus and Salmonella spp. [7]. Phages can be delivered topically, orally, directly into body tissues, or systemically.…”
Section: Phage Therapymentioning
confidence: 99%